2004
DOI: 10.1185/030079904125004060
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptors and schizophrenia

Abstract: The incidence of smoking is very high in non-schizophrenic subjects presenting various psychiatric disorders (35 to 54%). However, the incidence of smoking is extremely high in schizophrenic patients: 80% to 90%, versus 25% to 30% of the general population. Various studies have demonstrated that the use of tobacco transiently restores the schizophrenic patient's cognitive and sensory deficits. Smoking cessation also appears to exacerbate the symptoms of the disease. Post-mortem binding studies have revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 160 publications
1
77
0
Order By: Relevance
“…These findings, taken together with the idea that schizophrenia patients have a strongly increased likelihood of smoking (for reviews, see Dalack et al, 1998;Ripoll et al, 2004), have led to the 'self-medication hypothesis' that proposes that schizophrenia patients may attempt to transiently remedy otherwise deficient attentional processes; this effect, however, could vary depending on genetic background (Kumari and Postma, 2005). Prepulse inhibition studies also contribute to the view that neurocognitive dysfunction in schizophrenia could be based on a dysfunctional nAChR system: George et al (2006) demonstrated that tobacco smoking selectively enhances PPI deficits in schizophrenia and more recently it was also shown that nasally administered nicotine increases PPI in schizophrenia patients and healthy controls (Hong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These findings, taken together with the idea that schizophrenia patients have a strongly increased likelihood of smoking (for reviews, see Dalack et al, 1998;Ripoll et al, 2004), have led to the 'self-medication hypothesis' that proposes that schizophrenia patients may attempt to transiently remedy otherwise deficient attentional processes; this effect, however, could vary depending on genetic background (Kumari and Postma, 2005). Prepulse inhibition studies also contribute to the view that neurocognitive dysfunction in schizophrenia could be based on a dysfunctional nAChR system: George et al (2006) demonstrated that tobacco smoking selectively enhances PPI deficits in schizophrenia and more recently it was also shown that nasally administered nicotine increases PPI in schizophrenia patients and healthy controls (Hong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of nicotinic treatments for a variety of neuropsychiatric indications including schizophrenia has been suggested [78][79][80][81][82]. Attentional improvement by nicotinic agents may be a key therapeutic effect for these psychiatric disorders [83,84].…”
Section: The Potential Of Nicotinic Treatment For the Cognitive Impaimentioning
confidence: 99%
“…Neuronal nAChRs have been implicated in a variety of disease states, including Alzheimer's disease [8], schizophrenia [9], a genetically transmissible form of epilepsy [10], inflammation and pain [11], and the autoimmune disease myasthenia gravis [12]. As such, there is great interest in characterizing ligands that can discriminate between different subunit arrangements of this receptor.…”
Section: Introductionmentioning
confidence: 99%